2011
DOI: 10.3892/or.2011.1520
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of 18F-fluorodeoxyglucose positron emission tomography/computed tomography at delayed phase for diagnosis and prognosis of malignant pleural mesothelioma

Abstract: Abstract. Malignant pleural mesothelioma (MPM) has a poor prognosis, and conventional imaging modalities do not reflect the prognosis of MPM. In this study, the clinical significance of 18 F-fluorodeoxyglucose positron emission tomography/ computed tomography fusion imaging ( 18 F-FDG PET/CT) was evaluated for the differential diagnosis, staging and prognosis in MPM patients. Ninety patients who underwent 18 F-FDG PET/CT scanning due to a clinical diagnosis or suspicion of MPM prior to therapy were reviewed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 25 publications
3
25
0
1
Order By: Relevance
“…Though, this area had been FDG positive in PET imaging during the treatment, enhanced glucose metabolism was only seen at the time of relapse. FDG PET is known to be a sensitive diagnostic method for staging of mesothelioma in adults and a high uptake is correlated with an unfavorable prognosis [ 1 ] . Final prognosis is diffi cult to predict for our patient as reliable survival data for pediatric patients do not exist.…”
Section: Confl Ict Of Interestmentioning
confidence: 99%
“…Though, this area had been FDG positive in PET imaging during the treatment, enhanced glucose metabolism was only seen at the time of relapse. FDG PET is known to be a sensitive diagnostic method for staging of mesothelioma in adults and a high uptake is correlated with an unfavorable prognosis [ 1 ] . Final prognosis is diffi cult to predict for our patient as reliable survival data for pediatric patients do not exist.…”
Section: Confl Ict Of Interestmentioning
confidence: 99%
“…A number of previous studies [9,[13][14][15][16][17][18][19][20], mostly retrospective and observational, have considered the relationship between survival and PET measurements at baseline. Of these, 8 studies [13][14][15][16][17][18][19][20] with a total of 594 patients found that high SUVmax or TLG at baseline indicated worse survival, and one with 41 patients [9] found no relationship. Three studies have considered percentage change in SUVmax, TLG and MTV after chemotherapy; two [9,12] with a total of 64 patients found that a percentage reduction in TLG was indicative of better OS, while one [20] with 131 patients found a percentage reduction in SUVmax was related to longer OS.…”
Section: Discussionmentioning
confidence: 99%
“…In these numerous studies, attempts have been made to qualify and quantify the impact of the length of the injection-to-scan time interval on differentiating malignant processes from benign processes. As one might expect, the findings reported amongst these various investigators have been highly variable, with some supporting the use of delayed phase and dual-time-point diagnostic 18 F-FDG PET imaging approaches [66-77,81-84,86,87,91-93,95-100,103-108,110,111,113,114,117-122,124-128,131,133,134,136,138,141,143,146,149,152,153,155,157,160-163,165,167,169], and with others not [65,78,89,90,94,101,102,109,115,116,123,129,130,132,135,137,139,140,147,148,150,151,156,158,164,166,168]. …”
Section: Discussionmentioning
confidence: 99%